Neisseria bacilliformis is a periodontal pathogen exacerbating periodontitis by inducing nitric oxide production - Kim, Bo-Min; Lim, Yeonjin; Park, Somin; Im, Jintaek; Yun, Cheol-Heui; Kum, Kee-Yeon; Park, Ok-Jin; Han, Seung Hyun (Frontiers in Immunology, 2026)
Periodontitis, a chronic inflammatory disease, often causes alveolar bone loss. Neisseria bacilliformis is a Gram-negative bacterium that has been identified in periodontal patients, but its role in periodontitis remains unclear. In the present study, we examined whether N. bacilliformis exacerbates periodontitis in a mouse ligature-induced periodontitis (LIP) model and investigated its underlying molecular mechanism. Topical treatment with N. bacilliformis on maxillary second molar exacerbated alveolar bone loss and worsened epithelial and periodontal ligament damage. Histological analyses showed that N. bacilliformis increases tartrate-resistant acid phosphatase (TRAP)-positive osteoclasts and inducible nitric oxide synthase (iNOS) levels in the gingival tissue. Treatment with N. bacilliformis induced nitric oxide (NO) production in RAW 264.7 cells, which was inhibited by polymyxin B, implying that N. bacilliformis lipooligosaccharide (LOS) is a major etiologic agent in the inflammatory response. Indeed, LOS purified from N. bacilliformis enhanced NO production and iNOS expression, primarily with activating Toll-like receptor (TLR) 4 and partially activating TLR2. LOS administration into the disto-palatal papilla near the molar further aggravated periodontitis in the LIP mouse model. These results suggest that N. bacilliformis is a periodontal pathogen that exacerbates inflammation and alveolar bone loss, with its LOS acting as an important virulence factor via TLR2/4 activation, leading to the production of the inflammatory mediator NO.